Historical Study of the Ibn Abbas As-Salafy Islamic Boarding School in Sragen - Moh. Ashif Fuadi (Presscience, 2023)
This study discusses the history of the development of the Ibn Abbas As-Salafy Islamic Boarding School at Sragen, Cental Java, Indonesia which began with a discussion of history, dynamics and contributions to the religious field of the Boarding School from 2006 to 2020. The author uses historical research methods by selecting themes or topics, heuristics, source criticism, interpretation and historiography or historical writing. The research outlines historical facts that focus on primary data in the form of archives, written documents, and interviews with historical actors and witnesses and supported by relevant literature. The results of this study described the dynamics and contribution of the boarding school to the religious education of the Beku village community. The Boarding School experienced three periods of development. The journey began at the pioneering stage in 2000-2005, then continued in 2006-2012, which was a period of pesantren development, and in 2013-2020, it became the peak period which was marked by the progress of the education and infrastructure program of the Boarding School. The Boarding School has become a place for students to build a generation of Quranic memorizers and memorizers of the Qur'an. In addition, it has had a positive impact on the people of Beku village. The positive impact is in the form of forming a religious society in accordance with the Qur'an and as Sunnah through community education organized by the pesantren.